"Jesus saved an ex-con" : political activism and redemption after incarceration - Flores, Edward (Religion and social transformation., 2018)
"This book sheds light on how former gang members and formerly incarcerated persons wage campaigns to expend the rights of those with criminal records. While the use of religion to rehabilitate and redeem has been a cultural touchstone of the modern era, such religious outreach has typically been associated with an emphasis on private spirituality. By contrast, this book examines how formerly incarcerated persons utilize faith-based organizations and the public arena."--Book cover